A self-consistent, multivariate method for the determination of gas-phase rate coefficients, applied to reactions of atmospheric VOCs and the hydroxyl radical - J. T. Shaw; R. T. Lidster; R. T. Lidster; D. R. Cryer; N. Ramirez; F. C. Whiting; G. A. Boustead; L. K. Whalley; L. K. Whalley; T. Ingham; T. Ingham; A. R. Rickard; et al. (Atmospheric Chemistry and Physics, 2018)
Gas-phase rate coefficients are fundamental to understanding atmospheric chemistry, yet experimental data are not available for the oxidation reactions of many of the thousands of volatile organic compounds (VOCs) observed in the troposphere. Here, a new experimental method is reported for the simultaneous study of reactions between multiple different VOCs and OH, the most important daytime atmospheric radical oxidant. This technique is based upon established relative rate concepts but has the advantage of a much higher throughput of target VOCs. By evaluating multiple VOCs in each experiment, and through measurement of the depletion in each VOC after reaction with OH, the OH + VOC reaction rate coefficients can be derived. Results from experiments conducted under controlled laboratory conditions were in good agreement with the available literature for the reaction of 19 VOCs, prepared in synthetic gas mixtures, with OH. This approach was used to determine a rate coefficient for the reaction of OH with 2,3-dimethylpent-1-ene for the first time; k =  5.7 (±0.3)  ×  10−11 cm3 molecule−1 s−1. In addition, a further seven VOCs had only two, or fewer, individual OH rate coefficient measurements available in the literature. The results from this work were in good agreement with those measurements. A similar dataset, at an elevated temperature of 323 (±10) K, was used to determine new OH rate coefficients for 12 aromatic, 5 alkane, 5 alkene and 3 monoterpene VOC + OH reactions. In OH relative reactivity experiments that used ambient air at the University of York, a large number of different VOCs were observed, of which 23 were positively identified. Due to difficulties with detection limits and fully resolving peaks, only 19 OH rate coefficients were derived from these ambient air samples, including 10 reactions for which data were previously unavailable at the elevated reaction temperature of T =  323 (±10) K.